Youth and Church in Italy: “Divorce” Already or “Separation”? - Bogdan Stańkowski (Studia Paedagogica Ignatiana, 2019)
Armando Matteo, Tutti giovani, nessun giovane. Le attese disattese della prima generazione incredula, Piemme, Milano 2018, ss. 203.